Proficient exclusion of pesticide using humic acid-modified magnetite nanoparticles from aqueous solution. (17th November 2022) - Jangra, Arti; Kumar, Jai; Singh, Devender; Kumar, Harish; Kumar, Parvin; Kumar, Suresh; Kumar, Ramesh
Abstract: Extensive dispersal of the pesticides to shield the different types of vegetation from pests has increased the production but at the same it has resulted in an increase in environmental pollution. Consequently, it is necessary to eliminate these undesired pollutants from the environment. The current investigation offers the synthesis of humic acid-coated magnetite nanoparticles towards effective removal of the most common insecticide, imidacloprid, from aqueous solution using a batch adsorption method. These synthesized nanoparticles were characterized with the help of several analytical and spectroscopic techniques. To acquire the maximum conceivable adsorption, effects of different influencing parameters like pH of the solution, time of contact, concentration of pesticide solution, amount of adsorbent and temperature were also examined. Moreover, the kinetic studies were found to be in good agreement with a pseudo-second-order kinetic model supporting the occurrence of chemisorption phenomenon. Additionally, isotherm modeling proved that the adsorption process was in accordance with the Langmuir model of isotherm. Thermodynamic parameters depicted the endothermic and spontaneous behavior of the adsorption process. Desorption studies were also carried out to examine the reusability of these nano-adsorbents. These verdicts confirmed that the surface modified magnetite nanoparticles may be treated as proficient material for exclusion of imidacloprid from the aqueous solution. HIGHLIGHTS: Humic acid functionalized magnetite nanoparticles were employed as a proficient tool for the removal of pesticides from aqueous solution. Kinetic studies established the occurrence of chemisorption phenomenon. Monolayer adsorption was confirmed with the help of isotherm modeling. Thermodynamic studies confirmed the adsorption process to be endothermic and spontaneous in nature. Graphical Abstract